2006
DOI: 10.1152/physiolgenomics.00271.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of purified gastric ECL and parietal cells: identification of a novel pathway regulating acid secretion

Abstract: The gastric entero-chromaffin-like (ECL) cell plays a key regulatory role in peripheral regulation of acid secretion due to the release of histamine that stimulates acid secretion by the parietal cell. Studies in intact animals, gastric glands, and isolated cells after short-term culture have shown expression of stimulatory CCK2 and PAC1 and inhibitory SST2 and Gal1 receptors as well as histidine decarboxylase. However, the pattern of its gene expression as a neuroendocrine cell has not been explored. Comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 71 publications
3
46
0
1
Order By: Relevance
“…Apelin and APJ mediate a wide range of physiological actions, including angiogenesis (Cox et al, 2006;Eyries et al, 2008;Kasai et al, 2008;Kidoya et al, 2008), heart contractility, blood pressure regulation (Dai et al, 2006) and other effects (Sorhede Winzell et al, 2005;Lambrecht et al, 2006;Lago et al, 2007). Apelin and APJ are expressed on ECs of newly developing blood vessels during angiogenesis (Kidoya et al, 2008), and it has been reported that apelin expression is induced by hypoxia in ECs (Eyries et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Apelin and APJ mediate a wide range of physiological actions, including angiogenesis (Cox et al, 2006;Eyries et al, 2008;Kasai et al, 2008;Kidoya et al, 2008), heart contractility, blood pressure regulation (Dai et al, 2006) and other effects (Sorhede Winzell et al, 2005;Lambrecht et al, 2006;Lago et al, 2007). Apelin and APJ are expressed on ECs of newly developing blood vessels during angiogenesis (Kidoya et al, 2008), and it has been reported that apelin expression is induced by hypoxia in ECs (Eyries et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…23 Apelin and APJ mediate a wide range of physiologic actions, including angiogenesis, [24][25][26][27] heart contractility and blood pressure regulation, 28 appetite and drinking behavior, 29 immune responses, 30 and other effects. 31,32 Apelin and APJ are expressed on ECs of the newly developing blood vessels during angiogenesis, 24 and it has been reported that apelin expression is induced by hypoxia in ECs. 26 In vitro analysis revealed that apelin stimulates proliferation, migration, and tube formation of ECs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many receptors are expressed at relatively low levels but their increased expression relative to other regions of the GI tract indicates significant function in the gastric secretory epithelium. The success of this method has been previously shown during transcriptomal analysis of purified suspensions of individual cell types, such as parietal and enterochromaffin-like (ECL) cells compared with the primary mucosal digest of the gastric corpus mucosa, which gave new insights into the interaction between these two cell types, such as apelin and the apelin receptor or the main pathway for regulation of histamine levels in the ECL cell (43)(44)(45). Similar approaches have been used to isolate and characterize regulation of gene expression of primary gastrointestinal epithelial cells, especially gastric corpus mucosal cell suspensions (3,32,82), purified mouse gastric parietal cells (31,52), gastric chief cells (51), and gastric epithelial progenitor cells (50).…”
mentioning
confidence: 99%